2023
DOI: 10.1002/adma.202307680
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Antimicrobial Metal–Phenolic Network Nanoparticles with High Biocompatibility for Wound Healing

Rongxin Yu,
Hongping Chen,
Jian He
et al.

Abstract: Antibiotic‐resistant bacteria pose a global health threat by causing persistent and recurrent microbial infections. To address this issue, antimicrobial nanoparticles (NPs) with low drug resistance but potent bactericidal effects have been developed. However, many of the developed NPs display poor biosafety and their synthesis often involves complex procedures and the antimicrobial modes of action are unclear. Herein, a simple strategy is reported for designing antimicrobial metal‒phenolic network (am‐MPN) NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…aureus after Au@MPN and Au@MPN-BMP2 treatment (Figure g,h). This phenomenon suggested that the polyphenols of MPN increased the permeability of bacterial membranes and altered their fluidity, thereby enhancing the antibacterial effect of the nanoparticle composites. ,, …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…aureus after Au@MPN and Au@MPN-BMP2 treatment (Figure g,h). This phenomenon suggested that the polyphenols of MPN increased the permeability of bacterial membranes and altered their fluidity, thereby enhancing the antibacterial effect of the nanoparticle composites. ,, …”
Section: Resultsmentioning
confidence: 97%
“…This phenomenon suggested that the polyphenols of MPN increased the permeability of bacterial membranes and altered their fluidity, thereby enhancing the antibacterial effect of the nanoparticle composites. 24,41,42 3.3. Biocompatibility and Antioxidant Capability of Au@MPN-BMP2 Nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…26,52 For example, antimicrobial metal-phenolic network nanoparticles have been studied for use in wound healing, which identified that there were multiple antimicrobial modes of these polyphenolic NPs, including reactive oxygen species production, bacterial wall disruption, and quinoprotein formation. 53 So, the antibacterial properties of the MTA natural bio-adhesives were verified further. Firstly, the antibacterial activity of MA, TA, and MTA bio-adhesives was studied quantitatively using S. aureus and E. coli bacterial clearance.…”
Section: Antioxidant and Antibacterial Ability Of Natural Polyphenoli...mentioning
confidence: 95%
“…We believe that the mechanism of natural polyphenolic bio-adhesives mainly includes the bactericidal activity of natural extracts, as well as the multiple effects of the natural acid anhydride-polyphenol networks, including clearing the reactive oxygen species, inhibiting protein formation, and destroying bacterial structures. 53,54 Above all, the MTA natural adhesives had excellent antioxidant and antibacterial properties, which could further enhance the healing of infected wound.…”
Section: Antioxidant and Antibacterial Ability Of Natural Polyphenoli...mentioning
confidence: 99%
“…The self-assembly phenomenon of polyphenols with other ingredients has been reported recently. [13][14][15] Peng et al proved the existence of self-assembled submicroparticles in chrysanthemum tea infusion, wherein the polyphenols form submicroparticles with pectin. 16 Chen et al developed a metalphenolic assembly approach, which is primarily mediated by metal-phenolic complexes through coordination and hydrophobic interactions, yielding uniform and spherical nanoparticles (mostly <200 nm).…”
Section: Introductionmentioning
confidence: 99%